2021
DOI: 10.2196/27630
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Psychotherapy Intervention for Depression Among Older Adults Receiving Home Care: Qualitative Study of Participants’ Experiences

Abstract: Background Depression is common among homebound older adults. Internet-based cognitive behavioral therapy (iCBT) is a promising but understudied approach for treating depression among older adults with disabilities. Objective This study aims to understand the experiences of homebound older adults who participated in a pilot feasibility trial of an iCBT for depression. Methods The participants included 21 hom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Following technological progress, modern digital health interventions have become mainstream in medical and healthcare services. During the COVID-19 pandemic, the conventional medical and healthcare service mode (hospital outpatient service and routine healthcare projects) has been "devastating, " whereas modern digital health intervention technologies have developed rapidly (Table 2 and Figure 1) (117)(118)(119)(120)(121)(122).…”
Section: Digit-based Treatment Of Lldmentioning
confidence: 99%
See 1 more Smart Citation
“…Following technological progress, modern digital health interventions have become mainstream in medical and healthcare services. During the COVID-19 pandemic, the conventional medical and healthcare service mode (hospital outpatient service and routine healthcare projects) has been "devastating, " whereas modern digital health intervention technologies have developed rapidly (Table 2 and Figure 1) (117)(118)(119)(120)(121)(122).…”
Section: Digit-based Treatment Of Lldmentioning
confidence: 99%
“…Internet-based cognitive behavioral therapy (iCBT) has also been used to treat patients with LLD (122). The potential efficacy and cost-effectiveness of iCBT in the treatment of LLD were examined in randomized interventions with telephone-delivered CBT or telephone-delivered non-directive supportive therapy (NST) for patients with LLD.…”
Section: Digit-based Treatment Of Lldmentioning
confidence: 99%
“…The review comprised 17 research studies. 35 – 51 Of the papers, nine were qualitative studies, and eight were mixed-method studies with an analysis of qualitative data. The sample size ranged from 2 to 90.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies involving homebound older adults have shown that modifications to both contents (eg, adding aging-related themes) and web interface (website or app) are needed to improve adherence and engagement with iCBT [33,34]. These studies suggest that older adults had difficulty applying lessons when presented with content that failed to address aging-related topics and were less tolerant to poor usability issues, possibly due to a combination of age-related changes (eg, cognitive, vision, motor control, speech, and hearing), physical disabilities, and their lack of familiarity with modern technology.…”
Section: Althoughmentioning
confidence: 99%